Synthesis method of quaternary humic acid drought-resistant water-retaining agent

Through the free radical polymerization reaction of sodium humate and acrylic acid and other substances, a quaternary humic acid drought-resistant water-retaining agent is prepared, which solves the problems of complex synthesis and high cost of water-retaining agents, and achieves low-cost, safe and efficient water absorption performance, which is suitable for agriculture and other fields.

CN120682423APending Publication Date: 2025-09-23TOPSOIL BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510794149.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-13
Publication Date
2025-09-23

AI Technical Summary

Technical Problem

The existing water-retaining agents have complex synthesis processes, high costs, and the relationship between water absorption and salt tolerance is difficult to control, resulting in limited application scope and costs that are beyond the farmers' affordability.

Method used

Sodium humate is used as raw material, acrylic acid, polyacrylamide, NaOH and N,N'-methylenebisacrylamide are added to carry out free radical polymerization reaction in aqueous solution to prepare quaternary humic acid drought-resistant water-retaining agent.

Benefits of technology

A low-cost and simple synthesis process has been achieved, and the production is safe without the discharge of three wastes. The prepared water-retaining agent still maintains high water absorption performance in a high-salt environment, and is suitable for wide application in agriculture and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120682423A_ABST
    Figure CN120682423A_ABST
Patent Text Reader

Abstract

The invention provides a synthesis method of a quaternary humic acid drought-resistant water-retaining agent. The synthesis method comprises the following steps: dissolving sodium humate in water to obtain a sodium humate aqueous solution; adding acrylic acid into the sodium humate aqueous solution, and fully stirring to obtain a first solution; dropwise adding a NaOH aqueous solution into the first solution, fully stirring, then adding ammonium persulfate, then adding N, N '-methylene bisacrylamide, heating in a water bath to 75 DEG C, maintaining the temperature of 75 DEG C, reacting until the mixture forms a sticky substance, and stopping stirring when stirring cannot be carried out; and keeping the temperature of the sticky mass for 2-3 hours, taking out the product, putting the product into a dry culture dish, cutting into small blocks, drying, taking out and grinding to obtain the quaternary humic acid drought-resistant water-retaining agent. The synthesis method of the quaternary humic acid drought-resistant water-retaining agent, provided by the invention, has the advantages of safe reaction system, low production cost, simple synthesis process and easiness in industrialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of drought-resistant and water-retaining agents, and relates to a method for synthesizing a quaternary humic acid drought-resistant and water-retaining agent. Background Art

[0002] A water-retaining agent (SRA) is a water-swellable polymer containing numerous strongly hydrophilic functional groups such as carboxyl and hydroxyl groups and possessing a certain degree of cross-linking. It absorbs water rapidly, maintains saturation equilibrium time quickly, and absorbs water at rates ranging from tens to thousands of times its own mass. Furthermore, absorbed water resists easy evaporation with changes in ambient temperature and pressure. It exhibits excellent chemical resistance and is insensitive to factors such as light, heat, and electricity. More importantly, at high ambient temperatures, it releases surface moisture, maintaining plant survival and growth. These superior physical and chemical properties enable SRAs to play a multifaceted role in increasing yield, profitability, and efficiency in soil moisture conservation, soil improvement, soil fertility enhancement, and seedling survival in mining areas.

[0003] The main shortcomings of currently developed water-retaining agents include: 1) A significant discrepancy between theoretical and practical water absorption performance: The water absorption performance of a water-retaining agent reflects its application potential; the better the water absorption performance, the wider its application range. 2) Complex synthesis processes: Currently, water-retaining agents are primarily synthesized using aqueous solution polymerization and reverse suspension methods. These methods have significant drawbacks: limited space available for the reaction vessel and cumbersome subsequent product handling. 3) Research on the relationship between water absorption and salt tolerance is disconnected: While water-retaining agents reported in the literature or commercially available have high absorption efficiencies in deionized water, their efficiency decreases sharply when salt ions are present in the solution. Research has struggled to determine the relationship between water absorption efficiency and salt tolerance. 4) Excessive cost: Water-retaining agents are currently used in agriculture, medicine, construction, and other fields, with agriculture being a primary focus. However, commercially available water-retaining agents are generally expensive, and the large application areas in agricultural production make the investment in water-retaining agents far beyond the reach of farmers.

[0004] Humic acid, a complex, macromolecular organic compound found in nature, is extremely useful in agriculture, forestry, animal husbandry, fishery, industry, environmental protection, and medicine. Humic acid improves soil quality, increases fertilizer utilization, stimulates crop growth, regulates plant metabolism, and enhances plant resistance to stress. It also exhibits excellent chemical activity. Using it as a raw material to prepare humic acid-based water-retaining agents combines the advantages of both humic acid and water-retaining agents, and is of great significance to the development of modern water-saving agriculture and ecological restoration in my country. Summary of the Invention

[0005] The technical problem to be solved by this application is that existing synthetic water-retaining agents have disadvantages such as high cost, environmental impact, usage restrictions and unclear long-term effects.

[0006] In order to solve the above problems, the present application provides a method for synthesizing a quaternary humic acid drought-resistant water-retaining agent, comprising: dissolving sodium humate in water to obtain a sodium humate aqueous solution; adding acrylic acid to the sodium humate aqueous solution and stirring thoroughly to obtain a first solution; Adding NaOH aqueous solution dropwise to the first solution and stirring thoroughly, then adding ammonium persulfate and then N,N'-methylenebisacrylamide, heating in a water bath to 75°C, maintaining 75°C and reacting until the mixture forms a sticky mass and cannot be stirred; After the sticky mass is kept warm for 2-3 hours, the product is taken out and placed in a dry culture dish, cut into small pieces, dried, taken out and ground to obtain a quaternary humic acid drought-resistant and water-retaining agent.

[0007] The present invention uses low-cost sodium humate as a raw material, sequentially adds acrylic acid as a first copolymer monomer, polyacrylamide as a second copolymer unit, alkali (NaOH), an initiator, and N,N'-methylenebisacrylamide (MBA), a cross-linking agent, and conducts a free radical polymerization reaction in an aqueous solution to obtain a quaternary humic acid drought-resistant water-retaining agent product.

[0008] Furthermore, in the sodium humate aqueous solution, the volume ratio of the mass of the sodium humate to the water is 100 g to 150 g: 300 mL to 500 mL.

[0009] Furthermore, the mass ratio of the sodium humate solution to the acrylic acid is (400-450):(75-85).

[0010] Furthermore, the concentration of the NaOH aqueous solution is 0.2 g / mL.

[0011] Furthermore, the amount of the NaOH aqueous solution added is 50-60 mL.

[0012] Furthermore, the mass ratio of the sodium humate solution: acrylic acid: NaOH aqueous solution: ammonium sulfate: N,N'-methylenebisacrylamide is (400-450):(75-85):(10-12):(4-5):(1-2).

[0013] Furthermore, the drying temperature is 60° C. and the drying time is 6 to 8 h.

[0014] Furthermore, the synthesis method of the above-mentioned quaternary humic acid drought-resistant water-retaining agent is specifically as follows: S1. Weigh 100-150 g of sodium humate, add 300 mL of deionized water, and mechanically stir at room temperature until the sodium humate is basically dissolved to obtain a sodium humate solution; S2. Then, 75-85 g of acrylic acid was added to the sodium humate solution and stirred for 10 minutes to obtain a first solution; S3. Add 50-60 mL of 0.2 g / mL NaOH aqueous solution dropwise to the first solution, stir thoroughly, then add 4-5 g of ammonium persulfate, and then add 1-2 g of N,N'-methylenebisacrylamide. Heat in a water bath to 75°C, and maintain this temperature until the mixture forms a sticky mass and cannot be stirred; S4. Keep the sticky mass warm for 2-3 hours, take out the product, put it into a dry culture dish, cut it into small pieces of 5-19 mm, put it into a 60°C oven for drying, take it out and grind it to obtain a five-element humic acid drought-resistant water-retaining agent.

[0015] The technical effects of this application are: 1. The present invention uses low-cost sodium humate as raw material, sequentially adds the first copolymer monomer acrylic acid, the second copolymer unit polyacrylamide, etc., alkali (NaOH), an initiator, and a cross-linking agent N,N'-methylenebisacrylamide MBA, and conducts a free radical polymerization reaction in an aqueous solution to obtain a quaternary humic acid drought-resistant water-retaining agent product.

[0016] 2. The present invention provides a method for synthesizing a quaternary humic acid drought-resistant and water-retaining agent, which has a safe reaction system, low production cost, simple synthesis process, and is easy to industrialize.

[0017] 3. The method provided by the present invention is used for halogenation catalysis. Since the reaction system is closed and the reaction temperature is moderate, no three wastes are discharged during the preparation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the full XPS spectrum of sodium phytate raw material; Figure 2 This is the C 1s spectrum of sodium humate raw material; Figure 3 This is the O 1s spectrum of the sodium humate raw material; Figure 4 This is the full XPS spectrum of B1; Figure 5 is the C 1s spectrum of B1; Figure 6 is the O 1s spectrum of B1; Figure 7 is the FT-IR spectrum of B1; Figure 8 This is a summary of the thermal analysis of B1: (a) thermogravimetric analysis, (b) differential thermal analysis; Figure 9 These are the SEM images of B1: a) 500x magnification; b) 2000x magnification; c) 5000x magnification; d) 10,000x magnification; Figure 10 This is the full XPS spectrum of B2; Figure 11 is the C 1s spectrum of B2; Figure 12 is the O 1s spectrum of B2; Figure 13 is the FT-IR spectrum of B2; Figure 14 This is a summary of the thermal analysis of B2: (a) thermogravimetric analysis, (b) differential thermal analysis; Figure 15 These are the SEM images of B2: a) 500x magnification; b) 2000x magnification; c) 2000x magnification; d) 10,000x magnification; Figure 16 This is the full XPS spectrum of B3; Figure 17 is the C 1s spectrum of B3; Figure 18 is the O 1s spectrum of B3; Figure 19 This is a summary of the thermal analysis of B3: (a) thermogravimetric analysis, (b) differential thermal analysis; Figure 20 This is the full XPS spectrum of B4; Figure 21 is the C 1s spectrum of B4; Figure 22 is the O 1s spectrum of B4; Figure 23 is the FT-IR spectrum of B4; Figure 24 This is a summary of the thermal analysis of B4: (a) thermogravimetric analysis, (b) differential thermal analysis; Figure 25 This is the full XPS spectrum of B5; Figure 26 is the C 1s spectrum of 5; Figure 27 is the O 1s spectrum of B5; Figure 28 This is the FT-IR spectrum of B5; Figure 29 This is a summary of the thermal analysis of B5: (a) thermogravimetric analysis, (b) differential thermal analysis; Figure 30 This is the full spectrum of B6; Figure 31 is the C 1s spectrum of B6; Figure 32 is the O 1s spectrum of B6; Figure 33 This is the FT-IR spectrum of B6; Figure 34 This is a summary of the thermal analysis of B6: (a) thermogravimetric analysis, (b) differential thermal analysis; Figure 35 This is the full XPS spectrum of B7; Figure 36 This is a summary of the thermal analysis of B7: (a) thermogravimetric analysis, (b) differential thermal analysis; Figure 37 This is the full XPS spectrum of B8; Figure 38 This is a summary of thermal analysis of B8: (a) thermogravimetric analysis, (b) differential thermal analysis. DETAILED DESCRIPTION

[0019] The following embodiments of the technical solution of the present application will be described in detail with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application and are therefore only examples and are not intended to limit the scope of protection of the present application.

[0020] Example 1 Weigh 120 g of sodium humate into a 1 L three-necked flask, then add 300 mL of deionized water. Mechanically stir at room temperature until essentially dissolved. Then, add 75 mL of acrylic acid (79.5 g, 1.1 mol) and continue stirring for 10 minutes. Add 0.2 g / mL NaOH solution (55 mL, 11 g of NaOH, 0.275 mol) dropwise with thorough stirring. Then, add ammonium persulfate ((NH4)2S2O8, 4.2 g) and N,N′-methylenebisacrylamide. Heat in a water bath to 75°C and maintain this temperature until the mixture forms a viscous mass that cannot be stirred. After incubation for 2 hours, remove the product, place it in a dry Petri dish, cut it into 5-19 mm pieces, and dry it in a 60°C drying oven. Grind it, bag it, and store it for later use. This is designated B1.

[0021] Example 2 Weigh 120 g of sodium humate and 10 g of polyacrylamide into a 1 L three-necked flask. Add 300 mL of deionized water and mechanically stir at room temperature until essentially dissolved. Then, add 75 mL of acrylic acid (79.5 g, 1.1 mol) and continue stirring for 10 minutes. Add 0.2 g / mL NaOH solution (55 mL, 11 g of NaOH, 0.275 mol) dropwise with thorough stirring. Then, add ammonium persulfate ((NH4)2S2O8, 4.2 g) and N,N′-methylenebisacrylamide. Heat in a water bath to 75°C and maintain this temperature until the mixture forms a viscous mass that cannot be stirred. After incubating for 2 hours, remove the product, place it in a dry Petri dish, cut it into 5-19 mm pieces, and dry it in a 60°C drying oven. Grind it, bag it, and reserve it for future use. This is designated B2.

[0022] Example 3 Weigh 120 g of sodium humate and 10 g of chitosan into a 1 L three-necked flask. Add 300 mL of deionized water and mechanically stir at room temperature until essentially dissolved. Then, add 75 mL of acrylic acid (79.5 g, 1.1 mol) and continue stirring for 10 minutes. Add 0.2 g / mL NaOH solution (55 mL, 11 g of NaOH, 0.275 mol) dropwise with thorough stirring. Then, add ammonium persulfate ((NH4)2S2O8, 4.2 g) and N,N′-methylenebisacrylamide. Heat in a water bath to 75°C and maintain this temperature until the mixture forms a viscous mass that cannot be stirred. After incubating for 2 hours, remove the product, place it in a dry Petri dish, cut it into 5-19 mm pieces, and dry it in a 60°C drying oven. Grind it, bag it, and reserve it for future use. This is designated B3.

[0023] Example 4 Weigh 120 g of sodium humate and 10 g of cellulose into a 1 L three-necked flask, add 300 mL of deionized water, and mechanically stir at room temperature until essentially dissolved. Then, add 75 mL of acrylic acid (79.5 g, 1.1 mol) and continue stirring for 10 minutes. Add 0.2 g / mL NaOH solution (55 mL, 11 g of NaOH, 0.275 mol) dropwise with thorough stirring. Then, add ammonium persulfate ((NH4)2S2O8, 4.2 g) and N,N′-methylenebisacrylamide. Heat in a water bath to 75°C and maintain this temperature until the mixture forms a viscous mass that cannot be stirred. After incubating for 2 hours, remove the product, place it in a dry Petri dish, cut it into 5-19 mm pieces, and dry it in a 60°C drying oven. Grind it, bag it, and reserve it for future use. This is designated B4.

[0024] Example 5 Weigh 120 g of sodium humate and 10 g of sulfonated lignin into a 1 L three-necked flask. Add 300 mL of deionized water and mechanically stir at room temperature until essentially dissolved. Then, add 75 mL of acrylic acid (79.5 g, 1.1 mol) and continue stirring for 10 minutes. Add 0.2 g / mL NaOH solution (55 mL, 11 g of NaOH, 0.275 mol) dropwise with thorough stirring. Then, add ammonium persulfate ((NH4)2S2O8, 4.2 g) and N,N′-methylenebisacrylamide. Heat in a water bath to 75°C and maintain this temperature until the mixture forms a sticky mass that cannot be stirred. After incubating for 2 hours, remove the product, place it in a dry Petri dish, cut it into 5-19 mm pieces, dry it in a 60°C drying oven, remove it, grind it, and bag it for later use. This is designated B5.

[0025] Example 6 Weigh 120 g of sodium humate and 10 g of polyvinyl alcohol into a 1 L three-necked flask. Add 300 mL of deionized water and mechanically stir at room temperature until essentially dissolved. Then, add 75 mL of acrylic acid (79.5 g, 1.1 mol) and continue stirring for 10 minutes. Add 0.2 g / mL NaOH solution (55 mL, 11 g of NaOH, 0.275 mol) dropwise with thorough stirring. Then, add ammonium persulfate ((NH4)2S2O8, 4.2 g) and N,N′-methylenebisacrylamide. Heat in a water bath to 75°C and maintain this temperature until the mixture forms a viscous mass that cannot be stirred. After incubating for 2 hours, remove the product, place it in a dry Petri dish, cut it into 5-19 mm pieces, and dry it in a 60°C drying oven. Grind it, bag it, and reserve it for future use. This is designated B6.

[0026] Example 7 Weigh 120 g of sodium humate and 10 g of polyacrylamide into a 1 L three-necked flask. Add 300 mL of deionized water and mechanically stir at room temperature until essentially dissolved. Then, add 75 mL of acrylic acid (79.5 g, 1.1 mol) and continue stirring for 10 minutes. Add 0.2 g / mL NaOH solution (55 mL, 11 g of NaOH, 0.275 mol) dropwise with thorough stirring. Then, add ammonium persulfate ((NH4)2S2O8, 4.2 g) and N,N'-methylenebisacrylamide. Heat in a water bath to 75°C and maintain this temperature until the mixture forms a viscous mass that cannot be stirred. After incubating for 2 hours, remove the product, place it in a dry Petri dish, cut it into 5-19 mm pieces, and dry it in a 60°C drying oven. Grind it, bag it, and reserve it for future use. This is designated B7.

[0027] Example 8 Weigh 120 g of sodium humate and 10 g of lactic acid into a 1 L three-necked flask. Add 300 mL of deionized water and mechanically stir at room temperature until essentially dissolved. Then, add 75 mL of acrylic acid (79.5 g, 1.1 mol) and continue stirring for 10 minutes. Add 0.2 g / mL NaOH solution (55 mL, 11 g of NaOH, 0.275 mol) dropwise with thorough stirring. Then, add ammonium persulfate ((NH4)2S2O8, 4.2 g) and N,N′-methylenebisacrylamide. Heat in a water bath to 75°C and maintain this temperature until the mixture forms a viscous mass that cannot be stirred. After incubating for 2 hours, remove the product, place it in a dry Petri dish, cut it into 5-19 mm pieces, and dry it in a 60°C drying oven. Grind it, bag it, and reserve it for future use. This is designated B8.

[0028] The sodium humate raw material was subjected to XPS analysis, and the results are shown in Table 1.

[0029] Table 1 Element binding energy and chemical composition of sodium humate raw materials a Binding energy (eV), the value in parentheses is the atomic percentage (at%). According to the data in Table 1, we can see that: The theoretical molecular formula of sodium humate raw material is: C 75.18 O 19.05 Si 3.61 Na 2.15 , molecular weight is 1358.5452, mass percentage: C% = 66.46%, O% = 22.43%, Si% = 7.46%, Na% = 3.63%.

[0030] Depend on Figure 1 It can be seen that, except for the elements reported in Table 1 and N, the sodium humate raw material does not contain other impurity elements.

[0031] Depend on Figure 2 It can be seen that the peak with binding energy at 284.7 eV represents the saturated carbon on the alkyl chain (such as alkyl carbon, hybridization mode sp 3 The peak with a binding energy of 285.5 eV represents the carbon atom of the CO bond, while the peak with a binding energy of 288.3 eV represents the carbon atom of the carboxyl group. The molar ratio is alkyl carbon:CO carbon:carboxyl carbon = 37.42:49.78:12.80.

[0032] Depend on Figure 3It can be seen that the peaks at binding energies of 531.1 and 532.0 eV represent the oxygen on the CO bond and the oxygen on the C=O bond, respectively, 532.9 eV represents the oxygen on the hydroxyl group, and 535.7 eV represents the oxygen of water adsorbed by sodium humate.

[0033] B1 was subjected to XPS analysis, and the results are shown in Table 2.

[0034] Table 2 Element binding energy and chemical composition of B1 a Binding energy (eV), the value in parentheses is the atomic percentage (at%). According to the data in Table 2, we can see that: First, the theoretical molecular formula of B1 is: C 48.13 O 41.93 Na 9.16 S 0.78 , molecular weight is 1484.5165, mass percentage: C% = 38.93%, O% = 45.19%, Na% = 14.18%, S% = 1.68%.

[0035] Second, the nitrogen content in B1 is very low, but the presence of nitrogen can be seen in the full spectrum, indicating that the cross-linking agent plays a cross-linking role, but MBA is not the main component of the water-retaining agent.

[0036] Depend on Figure 4 It can be seen that, except for the elements reported in Table 2 and N, B1 does not contain other impurity elements.

[0037] Depend on Figure 5 It can be seen that the peak with binding energy at 284.8 eV represents the saturated carbon on the alkyl chain (such as alkyl carbon, hybridization mode sp 3 The peak with a binding energy of 286.2 eV represents the carbon atom of the CO bond, while the peak with a binding energy of 288.7 eV represents the carbon atom of the carboxyl group. The molar ratio is alkyl carbon:CO carbon:carboxyl carbon = 31.72:12.48:55.80.

[0038] Depend on Figure 6 It can be seen that the peaks at binding energies of 531.7 and 532.6 eV represent the oxygen on the CO bond and the oxygen on the C=O bond, respectively, 533.7 eV represents the oxygen on the hydroxyl group, and 536.1 eV represents the oxygen of adsorbed water.

[0039] The infrared spectrum of B1 is as follows Figure 7 As shown. Among them, at 3000-3500 cm -1The broad peak at 1635 cm represents the OH stretching vibration of the hydroxyl group in the water retaining agent or the OH stretching vibration of the hydroxyl group of the adsorbed water in the water retaining agent; -1 The peak at 1558 cm represents the stretching vibration of the C=O double bond; -1 The sharp peak represents the stretching vibration of the CO bond in the water retaining agent.

[0040] The thermal analysis of B1 is summarized by Figure 8 As shown. Figure 8 a As can be seen, B1 is between 100-150 o C slowly loses weight, which represents the loss of adsorbed water (and possibly a small amount of adsorbed gas or organic matter) contained in B1. The mass percentage of this part is 4.8%. o The weight loss percentage of C is 2.1%, which proves that B1 is stable under normal natural conditions. o The weight loss percentage of C is 11.5%, which represents the thermal decomposition and escape of organic matter contained in B1. o The weight loss percentage of C is 9.7%, which represents the thermal decomposition and escape of the more difficult-to-volatile organic matter contained in B1 (it is very likely that the organic matter is converted into a large amount of gas and escapes, showing a rapid weight loss state). Figure 8 b is visible, at 30-300 o During the heating process of C, B1 first releases heat and then absorbs heat, which means that the loss of adsorbed water (which may also include a small amount of adsorbed gas or organic matter) may be an exothermic process, but the heat loss of the organic matrix of B1 must be an endothermic process.

[0041] Depend on Figure 9 It can be seen that B1 is composed of particles of 0.2-5.0 μm (ad), and the particles are irregular polyhedrons.

[0042] B2 was subjected to XPS analysis, and the results are shown in Table 3.

[0043] Table 3 Element binding energy and chemical composition of B2 a Binding energy (eV), the value in parentheses is the atomic percentage (at%). According to the data in Table 3, we can see that: First, the theoretical molecular formula of B2 is: C 68.55 O 28.04 Na 3.41 , molecular weight is 1350.3214, mass percentage: C% = 60.96%, O% = 33.22%, Na% = 5.80%.

[0044] Second, the nitrogen content in B2 is very low, but the presence of nitrogen can be seen in the full spectrum, indicating that the cross-linking agent plays a cross-linking role, but MBA is not the main component of the water-retaining agent.

[0045] Depend on Figure 10 It can be seen that, except for the elements reported in Table 3 and N, B2 does not contain other impurity elements.

[0046] Depend on Figure 11 It can be seen that the peak with binding energy at 284.5 eV represents the carbon atoms on the benzene ring (hybridization mode sp 2 The peak with a binding energy of 286.0 eV represents the carbon atom in the CO bond, while the peak with a binding energy of 288.5 eV represents the carbon atom in the carboxyl group. The molar ratio is 60.97:20.46:18.57 for benzene ring carbon atom:20.46:18.57 for CO bond carbon atom.

[0047] Depend on Figure 12 It can be seen that the peaks at binding energies of 531.7 and 532.6 eV represent the oxygen on the CO bond and the oxygen on the C=O bond, respectively, while the peak at 535.6 eV represents the oxygen of the hydroxyl group in B2 or the oxygen of adsorbed water.

[0048] The infrared spectrum of B2 is as follows Figure 13 Among them, at 3500-3750 cm -1 The broad peak at 1635 cm represents the OH stretching vibration of the hydroxyl group in the water retaining agent; -1 The peak at 2800-2990 cm represents the stretching vibration of the C=O double bond; -1 The vibration of 1639 cm represents the CH stretching vibration of methyl and methylene in the water retaining agent; -1 The vibration of 1558 cm represents the stretching vibration of the C=O double bond; -1 The sharp peak represents the stretching vibration of the CO bond in the water retaining agent.

[0049] The thermal analysis of B2 is summarized by Figure 14 As shown. Figure 14 a As can be seen, B2 is between 30-150 o C weight loss represents the loss of adsorbed water (and possibly a small amount of adsorbed gas or organic matter) contained in B2, and the mass percentage of this part is 9.4%. o The weight loss percentage of C is 6.3%, which proves that B2 is basically stable under normal natural conditions. o The weight loss percentage of C is 10.5%, which represents the thermal decomposition and escape of organic matter contained in B2. oThe weight loss percentage of C is 17.1%, which represents the thermal decomposition and escape of the more difficult-to-volatile organic matter contained in B2 (it is very likely that the organic matter is converted into a large amount of gas and escapes, showing a rapid weight loss state). Figure 14 b is visible, at 30-300 o During the heating process of C, B2 first releases heat and then absorbs heat, which means that the loss of adsorbed water (which may also include a small amount of adsorbed gas or organic matter) may be an exothermic process, but the heat loss of the organic matrix of B2 must be an endothermic process.

[0050] Depend on Figure 15 It can be seen that B2 is composed of particles of 0.2-5.0 μm (ad, Fig. 18), and the particles are irregular polyhedrons.

[0051] B3 was subjected to XPS analysis, and the results are shown in Table 3.

[0052] Table 4 Element binding energy and chemical composition of B3 a Binding energy (eV), the value in parentheses is the atomic percentage (at%). According to the data in Table 4, we can see that: First, the theoretical molecular formula of B3 is: C 73.88 O 23.33 N 1.11 Na 1.11 S 0.56 , molecular weight is 1319.6024, mass percentage: C% = 67.23%, O% = 28.28%, Na% = 1.93%.

[0053] Second, B3 contains nitrogen, which means that the crosslinker MBA constructs the three-dimensional grid of the water-retaining agent; B3 contains a small amount of S, which comes from the initiator ammonium persulfate.

[0054] Depend on Figure 16 It can be seen that B3 does not contain other impurity elements except the elements reported in Table 4.

[0055] Depend on Figure 17 It can be seen that the peak with binding energy at 284.5 eV represents the carbon atoms on the benzene ring (hybridization mode sp 2 The peak with a binding energy of 285.9 eV represents the carbon atom in the CO bond (lower than 286.0, indicating the presence of a small amount of CN bond), while the peak with a binding energy of 288.3 eV represents the carbon atom in the carboxyl group. The molar ratio is 49.45:29.09:21.46 for benzene ring carbon atom:carbon atom in the CO bond:carbon atom in the carboxyl group.

[0056] Depend on Figure 18It can be seen that the peak at the binding energy of 531.7 eV represents the oxygen on the CO bond, while the broad peak at 535.6 eV represents the oxygen on the C=O bond and the oxygen of the hydroxyl group on the water retaining agent.

[0057] The thermal analysis of B3 is summarized by Figure 19 As shown. Figure 19 a As can be seen, B3 is between 30-150 o The weight loss of C can be attributed to the loss of adsorbed water (which may also include a small amount of adsorbed gas or organic matter) of B3, which has a mass percentage of 4.9%. o The weight loss percentage of C is 2.6%, which proves that B3 is stable under natural conditions. o The weight loss percentage of C is 31.0%, which represents the thermal decomposition and escape of organic matter contained in B3 (a large amount of organic matter is converted into gas and escaped, showing a rapid weight loss state). Figure 19 b can be seen, at 30 o C (2 min) -300 o During the heating process of C (18 min), B3 first released heat and then absorbed heat, indicating that the loss of adsorbed water (which may also include a small amount of adsorbed gas or organic matter) may be an exothermic process, but the heat loss of the organic matrix of B3 must be an endothermic process.

[0058] B4 was subjected to XPS analysis, and the results are shown in Table 5.

[0059] Table 5 Element binding energy and chemical composition of B4 a Binding energy (eV), the value in parentheses is the atomic percentage (at%). According to the data in Table 5, we can see that: First, the theoretical molecular formula of B4 is: C 69.14 O 21.66 Si 7.88 Na 0.91 S 0.41 , molecular weight is 1432.3461, mass percentage: C% = 57.97%, O% = 24.19%, Na% = 1.46%.

[0060] Second, the nitrogen contained in B4 comes from the raw material cellulose; B4 contains a small amount of S, which comes from the initiator ammonium persulfate.

[0061] Depend on Figure 20 It can be seen that B4 does not contain other impurity elements except the elements reported in Table 5.

[0062] Figure 21It can be seen that the peak with binding energy at 284.4 eV represents the carbon atoms on the benzene ring (hybridization mode sp 2 The peak with a binding energy of 285.8 eV represents the carbon atom in the CO bond, while the peak with a binding energy of 288.4 eV represents the carbon atom in the carboxyl group. The molar ratio is 64.47:19.97:15.55 for benzene ring carbon atom:19.97:15.55 for CO bond carbon atom.

[0063] Depend on Figure 22 It can be seen that the peak of binding energy at 531.6 eV represents the oxygen on the CO bond, while the broad peak at 532.5 eV represents the oxygen on the C=O bond, and the small peak at 535.7 eV represents the oxygen of the hydroxyl group on the water retaining agent or the hydroxyl oxygen of water adsorbed by the water retaining agent.

[0064] The infrared spectrum of B4 is as follows Figure 23 Among them, at 2850-2995 cm -1 The vibration of 1705 cm represents the CH stretching vibration of methyl and methylene in the water retaining agent; -1 The vibration of represents the stretching vibration of the C=O double bond; at 1565 cm -1 The sharp peaks represent the stretching vibration of CO bonds in water retaining agents. In addition, the peaks at 3000-3500 cm -1 There is no obvious absorption vibration peak, indicating that B4 contains very little water, which is consistent with the findings of the O 1s spectrum of B4 ( Figure 22 ).

[0065] The thermal analysis of B4 is summarized by Figure 24 As shown. Figure 24 a As can be seen, B4 is between 30-150 o The weight loss of C can be attributed to the loss of adsorbed water (which may also include a small amount of adsorbed gas or organic matter) of B4, which accounts for 5.2% of the mass percentage. o The weight loss percentage of C is 2.8%, which proves that B4 is stable under natural conditions. o The weight loss percentage of C is 7.0%, which represents the thermal decomposition and escape of organic matter contained in B4; o The weight loss percentage of C is 25.3%, which represents the thermal decomposition and escape of the high-boiling-point organic matter contained in B4 (the organic matter is converted into gas and escaped, showing a rapid weight loss state). Figure 24 b can be seen, at 30 o C (2 min) -300 o During the heating process of C (18 min), B4 first released heat and then absorbed heat, indicating that the loss of adsorbed water (which may also include a small amount of adsorbed gas or organic matter) may be an exothermic process, but the heat loss of the large amount of organic matter contained in B4 must be an endothermic process.

[0066] B5 was subjected to XPS analysis, and the results are shown in Table 6.

[0067] Table 6 Element binding energy and chemical composition of B5 a Binding energy (eV), the value in parentheses is the atomic percentage (at%). According to the data in Table 6, we can see that: First, the theoretical molecular formula of B5 is: C 71.47 O 22.90 Si 2.85 Na 2.54 S 0.24 , molecular weight is 1370.9002, mass percentage: C% = 62.61%, O% = 26.72%, Na% = 4.25%.

[0068] Second, B5 contains a small amount of S, which comes from the raw material sulfonated lignin.

[0069] Depend on Figure 25 It can be seen that B5 does not contain other impurity elements except the elements reported in Table 6.

[0070] Depend on Figure 26 It can be seen that the peak with binding energy at 284.6 eV represents the carbon atoms on the benzene ring (hybridization mode sp 2 ) and the carbon atoms on the alkyl carbon chain (hybridization pattern sp 3 The peak with a binding energy of 285.7 eV represents the carbon atom in the CO bond, while the peak with a binding energy of 288.4 eV represents the carbon atom in the carboxyl group. The molar ratio is 48.28:30.21:21.51 benzene ring (plus alkyl) carbon atom:CO carbon atom:carboxyl carbon atom.

[0071] Depend on Figure 27 It can be seen that the peak of binding energy at 531.4 eV represents the oxygen on the CO bond, while the broad peak at 532.6 eV represents the oxygen on the C=O bond, and the small peak at 534.8 eV represents the oxygen of the hydroxyl group on the water retaining agent or the hydroxyl oxygen of water adsorbed by the water retaining agent.

[0072] The infrared spectrum of B5 is as follows Figure 28 As shown. Among them, at 3000-3500 cm -1 The vibration of 1695 cm represents the vibration of hydroxyl groups in water retaining agent (functional groups of water retaining agent or hydroxyl groups of adsorbed water); -1 The vibration of represents the stretching vibration of the C=O double bond; at 1580cm -1 The sharp peak represents the stretching vibration of the CO bond in the water retaining agent.

[0073] The thermal analysis of B5 is summarized by Figure 29 As shown. Figure 29 a As can be seen, B5 is between 30-150 o The weight loss of C can be attributed to the loss of adsorbed water (which may also include a small amount of adsorbed gas or organic matter) of B5, which has a mass percentage of 5.5%. o The weight loss percentage of C is 2.7%, which proves that B5 is stable under natural conditions. o The weight loss percentage of C is 30.0%, which represents the thermal decomposition and escape of organic matter contained in B5. Figure 29 b can be seen, at 30 o C (2 min) -300 o During the heating process of C (18 min), B5 first released heat and then absorbed heat, indicating that the loss of adsorbed water (which may also include a small amount of adsorbed gas or organic matter) may be an exothermic process, but the heat loss of the large amount of organic matter contained in B5 must be an endothermic process.

[0074] B6 was subjected to XPS analysis, and the results are shown in Table 7.

[0075] Table 7 Element binding energy and chemical composition of B6 a Binding energy (eV), the value in parentheses is the atomic percentage (at%). According to the data in Table 7, we can see that: First, the theoretical molecular formula of B6 is: C 74.26 O 23.77 Na 1.38 S 0.59 , molecular weight is 1322.8242, mass percentage: C% = 67.42%, O% = 28.75%, Na% = 2.39%.

[0076] Second, B6 contains a small amount of S, which comes from the raw material MBA.

[0077] Depend on Figure 30 It can be seen that B6 does not contain other impurity elements except the elements reported in Table 7.

[0078] Depend on Figure 31 It can be seen that the peak with binding energy at 284.5 eV represents the carbon atoms on the benzene ring (hybridization mode sp 2 ) and the carbon atoms on the alkyl carbon chain (hybridization pattern sp 3The peak with a binding energy of 285.7 eV represents the carbon atom in the CO bond, while the peak with a binding energy of 288.4 eV represents the carbon atom in the carboxyl group. The molar ratio is 56.68:24.58:18.74 for benzene ring (plus alkyl) carbon atom:CO carbon atom:carboxyl carbon atom.

[0079] Depend on Figure 32 It can be seen that the peak of binding energy at 531.7 eV represents the oxygen on the CO bond, while the broad peak at 533.8 eV represents the oxygen on the C=O bond, and the small peak at 535.8 eV represents the oxygen of the hydroxyl group on the water retaining agent or the hydroxyl oxygen of water adsorbed by the water retaining agent.

[0080] The infrared spectrum of B6 is as follows Figure 33 Among them, at 3200-3500 cm -1 The vibration of hydroxyl groups in water retaining agents (functional groups of water retaining agents or hydroxyl groups of adsorbed water); at 2850-2950 cm -1 The peak at 1710 cm represents the CH stretching vibration of methyl or methylene; -1 The vibration of represents the stretching vibration of the C=O double bond; at 1550 cm -1 The sharp peak represents the stretching vibration of the CO bond in the water retaining agent.

[0081] The thermal analysis of B6 is summarized by Figure 34 As shown. Figure 34 a As can be seen, B6 is between 30-150 o The weight loss of C can be attributed to the loss of adsorbed water (which may also include a small amount of adsorbed gas or organic matter) of B6, which accounts for 7.5% of the mass percentage. o The weight loss percentage of C is 4.5%, which proves that B6 is basically stable under natural conditions. o The weight loss percentage of C is 38.8%, which represents the thermal decomposition and escape of organic matter contained in B6. Figure 34 b can be seen, at 30 o C (2 min) -300 o During the heating process of C (18 min), B6 ​​first released heat and then absorbed heat, indicating that the loss of adsorbed water (which may also include a small amount of adsorbed gas or organic matter) may be an exothermic process, but the heat loss of the large amount of organic matter contained in B6 must be an endothermic process.

[0082] B7 was subjected to XPS analysis, and the results are shown in Table 8.

[0083] Table 8 Element binding energy and chemical composition of B7 aBinding energy (eV), the value in parentheses is the atomic percentage (at%). According to the data in Table 8, we can see that: First, the theoretical molecular formula of B7 is: C 69.92 O 20.73 N 1.58 Na 0.97 Si 6.79 , molecular weight is 1406.5864, mass percentage: C% = 59.70%, O% = 23.58%, Na% = 1.58%.

[0084] Second, B7 contains a small amount of N, which comes from the raw material PVP.

[0085] Depend on Figure 35 It can be seen that B7 does not contain other impurity elements except the elements reported in Table 7.

[0086] The thermal analysis of B7 is summarized by Figure 36 As shown. Figure 36 a As can be seen, B7 is between 30-150 o The weight loss of C can be attributed to the loss of adsorbed water (which may also include a small amount of adsorbed gas or organic matter) of B6, which accounts for 5.6% of the mass percentage. o The weight loss percentage of C is 3.0%, which proves that B7 is stable under natural conditions. o The weight loss percentage of C is 41.4%, which represents the thermal decomposition and escape of organic matter contained in B7. Figure 36 b can be seen, at 30 o C (2 min) -300 o During the heating process of C (18 min), B7 first released heat and then absorbed heat, indicating that the loss of adsorbed water (which may also include a small amount of adsorbed gas or organic matter) may be an exothermic process, but the heat loss of the large amount of organic matter contained in B7 must be an endothermic process.

[0087] B8 was subjected to XPS analysis, and the results are shown in Table 9.

[0088] Table 9 Element binding energy and chemical composition of B8 a Binding energy (eV), the value in parentheses is the atomic percentage (at%). According to the data in Table 9, we can see that: First, the theoretical molecular formula of B8 is: C 70.27 O 23.00 S 0.39 Na 1.66Si 4.68 , molecular weight is 1394.0707, mass percentage: C% = 60.53%, O% = 26.39%, Na% = 2.73%.

[0089] Second, B8 contains a small amount of S, which comes from the raw material MBA.

[0090] Depend on Figure 37 It can be seen that B8 does not contain other impurity elements except the elements reported in Table 8.

[0091] The thermal analysis of B8 is summarized by Figure 38 As shown. Figure 38 a As can be seen, B8 is between 30-150 o The weight loss of C can be attributed to the loss of adsorbed water (which may also include a small amount of adsorbed gas or organic matter) of B8, which accounts for 5.1% of the mass percentage. o The weight loss percentage of C is 2.2%, which proves that B8 is stable under natural conditions. o The weight loss percentage of C is 39.6%, which represents the thermal decomposition and release of organic matter contained in B8. Figure 38 b can be seen, at 30 o C (2 min) -300 o During the heating process of C (18 min), B8 was always in an endothermic state, and at 13 min and 17 min, a sharp endothermic phenomenon occurred, indicating that the heat loss of the large amount of organic matter contained in B8 must be an endothermic process, and its structure is different from that of B1-B7.

[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for synthesizing a quaternary humic acid drought-resistant water-retaining agent, characterized in that: include: dissolving sodium humate in water to obtain a sodium humate aqueous solution; adding acrylic acid to the sodium humate aqueous solution and stirring thoroughly to obtain a first solution; Adding NaOH aqueous solution dropwise to the first solution and stirring thoroughly, then adding ammonium persulfate and then N,N'-methylenebisacrylamide, heating in a water bath to 75°C, maintaining 75°C and reacting until the mixture forms a sticky mass and cannot be stirred; After the sticky mass is kept warm for 2-3 hours, the product is taken out and placed in a dry culture dish, cut into small pieces, dried, taken out and ground to obtain a quaternary humic acid drought-resistant and water-retaining agent.

2. The method for synthesizing the quaternary humic acid drought-resistant water-retaining agent according to claim 1, characterized in that: In the sodium humate aqueous solution, the volume ratio of the mass of the sodium humate to the water is 100g~150g:300mL~500mL.

3. The method for synthesizing the quaternary humic acid drought-resistant water-retaining agent according to claim 1, characterized in that: The mass ratio of the sodium humate solution to the acrylic acid is (400-450):(75-85).

4. The method for synthesizing the quaternary humic acid drought-resistant water-retaining agent according to claim 1, characterized in that: The concentration of the NaOH aqueous solution is 0.2 g / mL.

5. The method for synthesizing the quaternary humic acid drought-resistant water-retaining agent according to claim 4, characterized in that: The amount of the NaOH aqueous solution added is 50-60 mL.

6. The method for synthesizing the quaternary humic acid drought-resistant water-retaining agent according to claim 4, characterized in that: The mass ratio of the sodium humate solution: acrylic acid: NaOH aqueous solution: ammonium sulfate: N,N'-methylenebisacrylamide is (400-450):(75-85):(10-12):(4-5):(1-2).

7. The method for synthesizing the quaternary humic acid drought-resistant water-retaining agent according to claim 1, characterized in that: The drying temperature is 60° C. and the drying time is 6 to 8 h.

8. The synthesis method according to claim 1, characterized in that Specifically: S1. Weigh 100-150 g of sodium humate, add 300 mL of deionized water, and mechanically stir at room temperature until the sodium humate is basically dissolved to obtain a sodium humate solution; S2. Then, 75-85 g of acrylic acid was added to the sodium humate solution and stirred for 10 minutes to obtain a first solution; S3. Add 50-60 mL of 0.2 g / mL NaOH aqueous solution dropwise to the first solution, stir thoroughly, then add 4-5 g of ammonium persulfate, and then add 1-2 g of N,N'-methylenebisacrylamide. Heat in a water bath to 75°C, and maintain this temperature until the mixture forms a sticky mass and cannot be stirred; S4. Keep the sticky mass warm for 2-3 hours, take out the product, put it into a dry culture dish, cut it into small pieces of 5-19 mm, put it into a 60°C oven for drying, take it out and grind it to obtain a five-element humic acid drought-resistant water-retaining agent.